100-Gb/s 3R Regeneration With Cross Gain Compression in Semiconductor Optical Amplifiers - Xin Chen; Li Huo; Qiang Wang; Caiyun Lou (IEEE Photonics Journal)
All optical 3R regeneration of 100-Gb/s return-to-zero on-off-keying (OOK) signal based on cross gain compression effect using semiconductor optical amplifiers is experimentally demonstrated for the first time. The shape of optical filters and signal powers are carefully adjusted to obtain the regenerative result. Bit error rate (BER) measurement is performed, and the receiving sensitivity is improved by 2 to 3 dB in the regenerative signal, compared with the degraded signal. Regenerative capability for different degrees of degradation has been studied.